1989
DOI: 10.1017/s000335610000386x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fish-meal supplementation on performance of overfat lambs fed on barley straw to reduce carcass fatness

Abstract: 1989). Effects of sh-meal supplementation on performance of overfat lambs fed on barley straw to reduce carcass fatness. Animal Production, 48, pp 131-138 ABSTRACT The effect of undegradable protein supply was studied in overfat lambs given low-energy diets to reduce carcass fatness. Two trials involving sequential batches of 48 overfat Suffolk x lambs investigated the effects of supplementing an ad libitum straw diet with either 0 or 100 g fish-meal pellets daily for 14-, 28-and 42-day periods. Lambs supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
2

Year Published

1993
1993
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 4 publications
(4 reference statements)
3
30
2
Order By: Relevance
“…5), similar to the observations by Vipond et al (1989). Absolute straw intake levels were also comparable to the results obtained by these workers.…”
Section: Feed Intake Refusals and Estimated Nutrient Uptakesupporting
confidence: 91%
See 4 more Smart Citations
“…5), similar to the observations by Vipond et al (1989). Absolute straw intake levels were also comparable to the results obtained by these workers.…”
Section: Feed Intake Refusals and Estimated Nutrient Uptakesupporting
confidence: 91%
“…There was no significant difference in CP content of refusals between weeks 2, 3, and 4. Vipond et al (1989) reported a very rapid acceptance of the fish meal supplementation by lambs in their experiment; this was not the scenario in our study.…”
Section: Feed Intake Refusals and Estimated Nutrient Uptakecontrasting
confidence: 55%
See 3 more Smart Citations